A Solid-State Luminescent Cd(II) Supramolecular Coordination Framework Based on Mixed Luminophores as a Sensor for Discriminatively Selective Detection of Amine Vapors - Sujitra Tunsrichon (2020)
Copyright © 2020 American Chemical Society. A novel Cd(II) supramolecular coordination framework containing mixed functionalized luminophore ligands, namely, [Cd(AS)2(phen)2]EtOH or 1 (where AS = 4-aminosalicylate, phen = 1,10-phenanthroline, EtOH = ethanol), was successfully synthesized as a solid-state luminescent sensor for the detection of amine vapors. The single-crystal X-ray diffraction analysis revealed that 1 possesses a three-dimensional (3D) supramolecular framework enclosing ethanol molecule in the lattice. The supramolecular structure is well-stabilized by various noncovalent intermolecular interactions through functional groups of ligands. Compound 1 shows an intense yellow solid-state emission and displays a reversibly discriminative luminescent response to NH3 and ethylenediamine (EDA) vapors through very large blue-shifted luminescent spectra with distinguishable emission colors under UV light. This work reports the first time for selective luminescent sensing of NH3 and EDA vapors with considerably different emission color change. A sensing mechanism has been confirmed by density functional theory and time-dependent density functional theory calculations that agrees well with the experimental results. Also, 1 exhibits a good recyclability over five cycles for sensing of NH3 and EDA vapors.